Pengaruh Penambahan Abu Sekam Padi dan Kapur Terhadap Tanah Lempung di Tawalian Timur Kabupaten Mamasa - Irwan Lie Keng Wong; Ika Apriyani; Erni Sriwinda (Paulus Civil Engineering Journal, 2023)
Land is a means of supporting buildings such as buildings, land transportation buildings, and aqueducts, as the land is used as the site where the building is built, so the power of the land affects the safety and comfort of the building. However, not all soils have good support, therefore, less good soils need to be stabilized by solidification or mixing of added materials that can improve soil properties such as cement, fly ash, lime, sand, and others. This study aims to determine the sliding angle of the mixture of rice and lime ash with some variation in the level of added ingredients and through direct shear, with reference to the American Society for Testing Materials (ASTM D3080). In this study, additional material was tested on a mixture of Lempung Soil using less than 50% gravel and sand soil. The methodology in this study is to be a reference and future evaluation to further develop rice husks and lime ash waste as an additional material for direct shear testing. Water content is 55.949%, land weight is 39.22 gr/cm3, land type weight 2.34 gr/cm3, brick boundary Atterbag liquid limit 54.40, plastic limit 40.53 and plastic index 13.67.